Requirements Specifications and Recovered Architectures as Grounded Theories - Daniel M. Berry; Michael W. Godfrey; Ric Holt; Cory J. Kapser; Isabel Ramos (Grounded Theory Review: An International Journal)
This paper describes the classic grounded theory (GT) process as a method to discover GTs to be subjected to later empirical validation. The paper shows that a well conducted instance of requirements engineering or of architecture recovery resembles an instance of the GT process for the purpose of discovering the requirements specification or recovered architecture artifact that the requirements engineering or architecture recovery produces. Therefore, this artifact resembles a GT.